Rare earth elements and fractionation of Zr-Hf and Y-Ho: implication to petrogenesis of idanre granite, Nigeria - Olagoke, Akinola O.; Azman A. Ghani; Elvaene James (Penerbit Universiti Kebangsaan Malaysia, 2021)
Idanre area which is situated within the Nigerian shield is affected by orogenic activities accompanied by emplacement of Pan-African granitoids. This paper presents a new information on geochemical behaviour of Rare Earth Elements (REEs) and High Field Strength Elements (HFSEs) Zr-Hf and Y-Ho that can explain post magmatic processes relating to the origin and evolution of the Idanre granite. Zr-Hf, Hf-(Zr/Hf) and Y-Ho, (Y/Ho)-Ho variation diagrams depicted similar mobility and migration patterns for Zr, Hf, Y and Ho. Binary plots of Log Zr/Hf vs Log Hf, Log Y/Ho vs Log Ho; high LREE/HREE and negative Eu anomaly shows extensive plagioclase and calcic amphibole fractionation. High Ce/Yb values 113.49, 134.97, and 123.6 reflects low partial melting in the source rocks. Similar Zr/Hf ratios 39.16; 39.3 and 43.26 for members of the granite suite suggest a common source for the minimally differentiated magmatic fluid. Y/ Ho ratios of 27.15, 27.12 and 25.91 indicate that the rock units are comagmatic. Mean Zr/Hf (41.69) and Y/Ho (27.18) ratios indicate the host migmatite may be the source rock for the Idanre granite complex.